Adipose tissue autophagy status in obesity: Expression and flux—two faces of the picture. Issue 3 (3rd March 2016) - Soussi, Hedi; Clément, Karine; Dugail, Isabelle
Abstract: In the context of elevated prevalence of obesity-associated metabolic diseases in the human population wordwide, interest in the autophagy degradation pathway is increasing, due to close links with energy metabolism, nutritional state, and inflammation. Here we highlight recent data focusing on adipose tissue which demonstrate alterations in fat cell autophagic flux in human obesity.